Investigation of the electrical limit conditions effects in piezoelectric transducer arrays utilized in medical imaging. (15th December 2020) - Laasri, Imane; Bybi, Abdelmajid; Mouhat, Ouadia; Jamal, Mohammad; Christine Hladky, Anne; Ettahir, Aziz; Kettani, Kamal
Highlights: Effects of the limit conditions on the physical behavior of the piezoelectric arrays. Crosstalk evaluation using both methods: parasitic voltages and displacements. Transducer array modeled by Finite Element method and characterized experimentally. Abstract: Crosstalk is considered as an undesirable phenomenon disturbing the electromechanical behavior of the ultrasonic transducer arrays used in medical imaging applications. Indeed, when one element of a transducer array is excited, it generates parasitic voltages and/or displacement fields on the adjacent passive elements. Consequently, these interactions between elements decrease the array's electroacoustic performance, which affects the obtained image quality. To overcome the crosstalk's problem, several research works propose active cancellation techniques. In this case, the correction voltages are determined by considering the array's elements grounded, contrary to the conventional crosstalk's definition which considers the array elements in Open-Circuit. The novelty of this paper is in one hand the study of the electrical limit conditions' effects on the physical behavior of a piezoelectric transducer array radiating in a fluid medium (water). On the other hand, a displacement method is proposed to evaluate the crosstalk level when the array elements are grounded. The limitations of the proposed method are also discussed. For this purpose, a piezoelectric transducer array is firstly modeled using a Two-dimensional Finite Elements Method (FEM), when the array elements are not grounded (open-circuit). Then, the results are compared to those obtained when the neighboring elements are grounded (as in the case of the crosstalk's active cancellation techniques). Finally, measurements are realized on a fabricated transducer array vibrating in air medium and are successfully compared to the results predicted using FEM.